Agro farmer's implementation towards the application of kitosanplus in Terengganu. Issue 1 (May 2021) - Zul Ariff, A L; Mohammad Amizi, A; Zulhazman, H; Aweng, E R; Nursalwani, M
Abstract: Agriculture sector remains as one of the important sectors that contribute to Malaysia's economy. The usage of Kitosanplus could represent an innovative eco-friendly strategy for managing plant diseased and replacing copper as it is consisting with an active molecule which could provide variety of application towards agriculture sector. The Kitosanplus is an active molecule that finds many possible applications in agriculture to reduce or replace more environmentally damaging chemical pesticides. The purpose of this study is to determine the most influential factor of agrofarmer towards Kitosanplus applications in Terengganu, Malaysia. The most popular agriculture activities in this area are paddy plantation followed by chilies. A survey conducted towards 50 respondent by distributing the questionnaires using purposive sampling technique which have the background of agrofarmer including the owner and the manager of the farms. The data then were analysed using SPSS Software. Based on the result, the implementation of agrofarmers towards Kitosanplus applications are influenced by their attitude.